2007
DOI: 10.1111/j.1600-0609.2007.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

The heart in transfusion dependent homozygous thalassaemia today – prediction, prevention and management

Abstract: Cardiac disease remains the major cause of death in thalassaemia major. This review deals with the mechanisms involved in heart failure development, the peculiar clinical presentation of congestive heart failure and provides guidelines for diagnosis and management of the acute phase of cardiac failure. It emphasizes the need for intensive medical – cardiac care and aggressive iron chelating management as, with such approaches, today, the patients outcomes can be favourable in the long term. It covers advances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 92 publications
1
51
0
2
Order By: Relevance
“…Excess iron accumulation is a leading cause of clinical deterioration and often death. 3 The emergence of new iron chelators has a major impact on the treatment of thalassemia major. Moreover, the availability of more than one iron chelators opens up the possibility of reducing iron overload of specific organs while enhancing its overall excretion.…”
mentioning
confidence: 99%
“…Excess iron accumulation is a leading cause of clinical deterioration and often death. 3 The emergence of new iron chelators has a major impact on the treatment of thalassemia major. Moreover, the availability of more than one iron chelators opens up the possibility of reducing iron overload of specific organs while enhancing its overall excretion.…”
mentioning
confidence: 99%
“…Although myocyte dysfunction due to iron overload is the single most important cause of cardiac complications in thalassaemia, previously there was a significant incidence of myocarditis (4% of a sample population), (26) although both conditions are much less common now, presumably due to improved treatment. (27) The baseline haemodynamic state associated with thalassaemia affects the clinical assessment of patients and can complicate the diagnosis of ventricular dysfunction. Knowledge of these characteristics is important and informs the appropriate use of standard treatments of ventricular failure.…”
Section: Clinical Cardiovascular Manifestations Of Thalassaemiamentioning
confidence: 99%
“…Several different studies with cardiomyocytes in culture have revealed that the toxicity caused by the iron profoundly modifies the contractility and electrophysiological behavior of these cells, and that these abnormalities are probably associated with elevated peroxidation of cellular membrane lipids. 98,101 There is also an increased incidence of thromboembolic events in β-thalassemia. This state of hypercoagulability can Several functional pulmonary abnormalities are described in β-thalassemic patients, which appear, in part, to be caused by iron deposits, generation of free hydroxyl radicals, connective tissue and alveolar capillary membrane abnormalities.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Hypercoagulability, platelet thromboembolism and possible reductions in NO have also been associated with the pulmonary hypertension observed in thalassemic patients, and which is more pronounced among those who have undergone splenectomy. 84,97,98,[101][102][103][104][105] The type of mutation to the β gene is associated with the clinical severity of the disease. 7 Thus, β + -IVS-I-6 mutation, known as the Portuguese type, is related with a more benign clinical course, whereasβ 0 39 corresponds with a more severe clinical course.…”
Section: Pathophysiologymentioning
confidence: 99%